Fertility Knowledge Among Women Struggling to Conceive Without Medical Intervention: A Brief Report - Halleran, Maria; Chernoff, Andie; Gordon, Jennifer L. (Frontiers in Global Women's Health, 2022)
Introduction Approximately 1 in 6 women experience infertility. Though medical treatments for infertility exist, they are very costly and highly burdensome for women. It is therefore desirable to optimize women's chances of conception without medical intervention by ensuring that they have adequate knowledge of the female menstrual cycle and the timing of the fertile window. The current study therefore aimed to assess the degree to which women struggling to conceive without medical intervention are knowledgeable about these topics. Methods One hundred and two women of reproductive age (18–45 years old) in Canada and the United States who had been struggling to conceive without medical intervention for ≥12 months completed an online survey including a questionnaire assessing knowledge related to reproduction and fertility. Results Mean accuracy score on the Fertility Knowledge Questionnaire was 67%. Seventy-two women were not aware that the week before ovulation was associated with the highest chances of conception. Women using cervical mucus tracking to increase chances of conception were more knowledgeable (p = 0.02), as were women with more formal education (p = 0.01). Conversely, women who had been attempting to conceive for longer had lower fertility knowledge (p = 0.03). Age, number of children, and family income were unrelated to fertility knowledge (p > 0.05). Discussion Our findings suggest that women who are struggling to conceive would benefit from education related to the timing and identification of the fertile window. Reproductive and primary healthcare providers can play an important role in assessing fertility knowledge and addressing knowledge gaps to improve chances of successful conception.